MR elastography detection of early viscoelastic response of the murine hippocampus to amyloid β accumulation and neuronal cell loss due to Alzheimer's disease. Issue 1 (19th April 2017) - Munder, Tonia; Pfeffer, Anna; Schreyer, Stefanie; Guo, Jing; Braun, Juergen; Sack, Ingolf; Steiner, Barbara; Klein, Charlotte
Abstract : Purpose: To investigate in vivo viscoelastic parameters related to early histopathological changes in the hippocampus and the cortex in early, preclinical Alzheimer's disease (AD) stages. Materials and Methods: Magnetic resonance elastography (MRE) was applied to female APP23 mice, an established transgenic mouse model of AD, at three different stages early in disease progression. To investigate the potential therapeutic effects of physical, cognitive, and social stimulation on brain viscoelasticity and histopathological characteristics, MRE was also applied after exposing young APP23 mice to environmentally enriched cage conditions (ENR), for 1, 12, or 24 weeks, which corresponds to adolescent, young‐adult, and adult age at the time of analysis. Results: Viscosity in the hippocampus of APP23 mice is lower than in controls (CTR) ( P = 0.005) and does not increase with age, as in CTR mice (adolescent vs. young‐adult: P = 1.000, vs. adult: P = 0.493, young‐adult vs. adult: P = 1.000). Hippocampal cell numbers decrease with disease progression in APP23 mice ( P < 0.001). Elasticity in the hippocampus is also reduced in APP23 mice ( P = 0.024) but increases ( P = 0.027) with disease progression. ENR in APP23 mice transiently increased hippocampal cell numbers ( P = 0.002) but not viscosity ( P = 0.838). Conclusion: MRE detects alterations in viscoelasticity in the hippocampus related to early histopathological changes in the APP23 mouse model of AD. Level of Evidence: 1 Technical Efficacy: Stage 2 J. Magn. Reson. Imaging 2018;47:105–114.